Respiratory Distress in Full Term Outborn Neonates: A Hospital Based Study - Naoom, Manal B.; Abdul-Zahra, Ahmed A.; Alsaadi, Yasir A. (Journal of the Faculty of Medicine Baghdad, 2013)
Summary:Background: Respiratory distress remains a major problem post adaptation and one of the most common reasons for admission of neonates to Intensive Care.Objectives: To study the causes and short term outcomes of respiratory distress in full term neonates and its correlation to mode of delivery.Patients and Methods: A cross sectional study was carried out on 100 full termoutborn neonates with respiratory distress admitted to Neonatal care unit of Children Welfare Teaching Hospital, Medical City, Baghdad from 1st of April to 31st of August 2011.Results: Hundred full term neonateswerestudied, 66% were boys and 81% born by cesarean section (elective cesarean sectionin 62%). In both sexes, Transient TachypneaofNewbornand pneumothorax ranked the 1st and 2nd among other causes.Among boys, early onset sepsis/pneumonia ranked 3rd, whereas late pneumonia and hyaline membrane disease among girls.The proportion ofTransient TachypneaofNewborn was higher in those who were delivered by cesarean section(86.66%).There was no significant correlation between the mode of delivery and respiratory distress in congenital heartdisease, birth asphyxia, meconium aspiration andtracheoesophagel fistula.The case fatality was 100% in birth asphyxia, 16.66% in sepsis/pneumonia, 9.09% in hyaline membrane disease and 5.88%in pneumothorax.Conclusions:Transient tachypnea was the commonest cause of hospitalizations among term neonates with respiratory distress. Elective cesarean sectionwas correlated with neonatal respiratory distress.Key Words: Respiratory Distress, Full Term Outborn neonates